2016
DOI: 10.1007/s00345-016-1934-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bladder cancer after radiation for prostate cancer as a function of time and radiation modality

Abstract: The increased risk of BlCa after prostate radiation occurs predominantly after 10 years, regardless of ethnicity. The RR of developing BlCa after 10 years is significantly higher following brachytherapy than after EBRT or EBRT and brachytherapy. Bladder cancers after prostate radiation, especially after brachytherapy, are generally lower stage but higher grade than those in patients without PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…They observed no excess risks for 0.5-1 years, and they did report excess risks for the periods 1-5 years, 5-10 years, and 10+ years. Several studies showed in particular an increased risk for radiation-induced SPC for the period after 10 years of follow-up (9,10). However, in a PCa population with most cases aged between 60-80 years, especially excess SPC risks in the first 10 years are important since they will have eventually have the most impact on survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed no excess risks for 0.5-1 years, and they did report excess risks for the periods 1-5 years, 5-10 years, and 10+ years. Several studies showed in particular an increased risk for radiation-induced SPC for the period after 10 years of follow-up (9,10). However, in a PCa population with most cases aged between 60-80 years, especially excess SPC risks in the first 10 years are important since they will have eventually have the most impact on survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous cohort studies in the 3DCRT era have addressed SPC risks in PCa survivor cohorts. They consistently reported limited excess SPC risks for mainly bladder and rectal cancer (6,7,9,10). The impact of IMRT dose distributions on SPC risks is a topical research question, addressed in many recent model studies, evaluating risks for different age categories and different IMRT features.…”
Section: Introductionmentioning
confidence: 99%
“…Some important limitations of the present study are acknowledged. First and foremost, the study has the limitations of similar retrospective SEER database studies . Moreover, it is plausible that additional biases that originate from variables that are not included in the SEER database remained unaccounted for.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Newcastle-Ottawa Quality Assessment Form for Cohort Studies, 12 studies had good qualities [14][15][16][17][18][19][20][21][22][23][24][25] and 14 studies have categorized in fair quality [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. (Supplement Fig.…”
Section: Quality Assessmentmentioning
confidence: 99%